Technology acceptance and purchase intention towards movie mobile advertising among youth in Malaysia - Abu Bakar, Mohd Syuhaidi; Bidin, Rosmiza (Elsevier, 2014)
The study identified the relationships between technology acceptance and purchase intentions on movie mobile advertising among youth Twitter users in Malaysia. Technology Acceptance Model was used to predict the acceptance of computer-based technology based on technology use and usefulness among the group age in various fields. The objective of this study is to investigate the relationship between technology acceptance (use and usefulness) towards movie mobile advertising in Malaysia and purchase intention. Data was collected from 400 Twitter users in Malaysia using snowball sampling and was analyzed with statistical analysis (SPSS) using descriptive and correlation analysis. The findings of this paper advocate that technology acceptance; use and usefulness in movie mobile advertising contributed significantly towards movie purchase intention among youth aged 15 to 29 in the country. This paper introduces the contribution of use and usefulness in the study of communication utilizing mobile telecommunication technology among youth in Malaysia.